Did the Commodities Prices Spike Increase Poverty in Aceh Province, Indonesia? - Nur, Rasyidusman Hannamara Furqan (Indonesian Journal of Multidisciplinary Science, 2026)
The global food price spikes of 2006–2008 and the subsequent surge in 2010–2011 raised serious concerns about poverty, as poor households are the most vulnerable to rising food costs. Aceh, which continues to face relatively high poverty rates and post-disaster recovery challenges, provides a relevant context to examine this issue. This study analyzes the impact of food commodity price shocks on household poverty, particularly the poverty gap, in Aceh Province. Methods: A quantitative panel-data approach is employed using three waves of SUSENAS data from 2008 to 2010. The model is estimated using a fixed-effects regression technique. Explanatory variables include household characteristics (household size, number of children, education, age, credit access, and employment sector) and prices of selected food commodities. The findings indicate that rising prices of externally supplied commodities, especially rice, eggs, and chili, tend to increase the poverty gap by raising household consumption costs. In contrast, higher prices of locally produced commodities such as mackerel/tuna fish, salt, and coffee may reduce the poverty gap through income gains for producer households. Credit access is associated with a reduction in the poverty gap, whereas larger household size increases poverty depth. Education and age of the household head contribute to lowering the poverty gap. Policy interventions focusing on food price stabilization, strengthening local commodity value chains, expanding productive credit access, adaptive social protection, and promoting non-agricultural employment diversification are essential to mitigate the poverty effects of food price shocks in Aceh.